Analisis Sistem Inventory Suku Cadang Truk (Studi Kasus: Bengkel DLH Kota Surabaya) - Nugroho, Adji Syafuly; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This research examines the truck spare parts inventory system at the Surabaya City Environmental Service (DLH) with the aim of increasing the operational availability of the waste transport fleet. The approach used includes ABC analysis to group spare parts based on annual consumption value, as well as MTBF (Mean Time Between Failure) and MTTR (Mean Time To Repair) calculations to assess the level of fleet reliability. Research findings show that around 73% of annual consumption value is concentrated in Class A parts—such as engine oil, inner tubes, and batteries—which are included in the fast-moving parts category. Apart from that, there are significant differences in the level of fleet reliability, with the highest MTBF value reaching 1440 hours and the lowest 270 hours. Based on these results, the study recommends implementing inventory control strategies tailored to the spare part class to reduce downtime and ensure smooth transportation operations.